2023
DOI: 10.3390/ijms24043522
|View full text |Cite
|
Sign up to set email alerts
|

Secretome of Adipose-Derived Stem Cells Cultured in Platelet Lysate Improves Migration and Viability of Keratinocytes

Abstract: Chronic wounds depict a silent epidemic challenging medical professionals worldwide. Regenerative medicine uses adipose-derived stem cells (ADSC) in promising new therapies. In this study, platelet lysate (PL) as a xenogen-free substitute for foetal bovine serum (FBS) in ADSC culture was used to create an ADSC secretome containing cytokines for optimal wound healing conditions. The ADSC secretome was tested on keratinocytes for migrational behaviour and viability. Therefore, human ADSC were characterized under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Studies have explored various methods to augment the healing capabilities of ADSCs. For instance, Hermann et al [ 56 ] found that incorporating platelet lysate into ADSC culture improved keratinocyte migration and viability. Carolina Oses et al [ 57 ] demonstrated that preconditioning ADSCs with Deferoxamine, a hypoxic mimetic, increased the secretion of neuroprotective and angiogenic factors.…”
Section: Progress On Enhancing Adsc Efficacy In Diabetic Foot Treatmentmentioning
confidence: 99%
“…Studies have explored various methods to augment the healing capabilities of ADSCs. For instance, Hermann et al [ 56 ] found that incorporating platelet lysate into ADSC culture improved keratinocyte migration and viability. Carolina Oses et al [ 57 ] demonstrated that preconditioning ADSCs with Deferoxamine, a hypoxic mimetic, increased the secretion of neuroprotective and angiogenic factors.…”
Section: Progress On Enhancing Adsc Efficacy In Diabetic Foot Treatmentmentioning
confidence: 99%
“…[6,7] During the granulation process of tissue development, various immune cells, including macrophages, mast cells, and T lymphocytes, secrete FGFs, leading to an increased FGF concentration at the wound site. [8][9][10] In turn, this promotes the growth of fibroblasts, epithelial cells, and keratinocytes, facilitating angiogenesis, epithelialization, and collagen formation, all of which contributes to promoting the wound healing process. [11][12][13][14] FGF7 is widely regarded as a significant growth factor for wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…MSCs have the potential to transform into skin substitutes, thereby acting as a viable alternative to dermal fibroblasts in the process of epidermis generation and skin wound healing. They are capable of differentiating into several cell types in injured areas, including dermal fibroblasts, keratinocytes, and endothelial cells ( Hermann et al, 2023 ; Mahmoudvand et al, 2023 ; Nilforoushzadeh et al, 2023 ). Apart from their differential ability, MSCs have additional characteristics, such as being easily harvested and showing minimal immunogenicity.…”
Section: Introductionmentioning
confidence: 99%